Euro area sovereign yields and the power of unconventional monetary policy - Afonso, António (2019)
We assess the determinants of long-term sovereign yield spreads, vis-à-vis Germany, using a panel of 10 Euro area countries over the period 1999.01–2016.07 notably regarding the ECB’s conventional and unconventional monetary policies. Our findings indicate that the international risk, the bid-ask spread and real effective exchange rate increased the 10-year sovereign bond yield spreads, while sovereign ratings’ improvements decreased the spreads. Moreover, Longer-term Refinancing Operations and the Securities Market Program decreased the yield spreads. The overall announcements of the unconventional policies also significantly decreased the yield spreads, notably in the periphery countries.